Host cellular protein RAB33B facilitates influenza viral replication and modulates M2 trafficking by enhancing autophagy - Shaotang Ye; Zhen Wang; Gang Lu; Aolei Chen; Liang Xu; Yongbo Liu; Jianwei Mao; Jingyu Wang; Gaoming Lou; Qingmei Xie; Kun Jia; Shoujun Li (Veterinary Research)
Abstract Influenza A virus (IAV) remains a major global health threat. Its M2 protein plays crucial roles in viral fusion, transportation, assembly, and release. Recent studies have shown that IAV impairs host autophagy flux to enhance viral replication. However, the precise mechanisms by which IAV M2 manipulates host cellular autophagy during virus replication remain unclear. In this study, we analysed cellular transcriptional responses of cells to IAV M2 overexpression and identified RAB GTPase protein RAB33B as a key factor. RAB33B was significantly up-regulated by IAV M2 and promoted IAV replication by enhancing autophagy. We further found that autophagy regulates the interaction of IAV M2, RAB33B, and LC3, facilitating M2 membrane trafficking through autophagic-like vesicles. In addition, ATG16L1 (an effector of RAB33B) and TBC1D25 (a GTPase-activating protein for RAB33B) contributed to IAV M2-induced autophagy, thereby affecting viral replication. Collectively, our findings reveal a novel mechanism in which RAB33B is essential for IAV M2 trafficking to the plasma membrane, facilitating viral replication through enhanced autophagy. These insights shed new light on the autophagy-based cellular transport mechanisms of IAV M2 and highlight potential antiviral targets.